2019
DOI: 10.29333/iji.2019.12435a
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration TPS Learning Model and m-Learning Based on Android for Understanding of Trigonometry Concepts with Different Cognitive Style

Abstract: This research aimed to examine the effect of collaboration Think Pair Share (TPS) Leaning Model and m-Learning based on Android on the understanding of trigonometry concepts and to investigate the interaction between collaborative learning and cognitive style on the understanding of trigonometry concepts. This research involved 80 pre-service teachers of Mathematics Department at STKIP Santu Paulus Ruteng, Province of East Nusa Tenggara, Indonesia. The quasiexperimental research with control class without pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…This is supported by the statement that trigonometry is an essential topic and cannot be separated from mathematics topic at the high school level (Huda & Qohar, 2021;Jelatu, Kurniawan, Kurnila, Mandur, & Jundu, 2019;Kamber & Takaci, 2018;Yang & Sianturi, 2017). The topic of trigonometry also has an important role outside the field of mathematics education, namely contributing to the development of science and technology and in everyday life such as measuring the height of buildings or buildings, flight engineering, helping to create a robot, and playing a role in the health sector (Emmanouil, Wei, & Dai, 2016;Goel, 2015;Jelatu et al, 2019;Mulyawati, Salmawati, Subianto, & Wafdan, 2017;Yang & Sianturi, 2017). In addition, the trigonometry topic has an important role because it is the topic that is tested as the final assessment in learning mathematics (Brijlall & Niranjan, 2015;Law, Shahrill, & Mundia, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…This is supported by the statement that trigonometry is an essential topic and cannot be separated from mathematics topic at the high school level (Huda & Qohar, 2021;Jelatu, Kurniawan, Kurnila, Mandur, & Jundu, 2019;Kamber & Takaci, 2018;Yang & Sianturi, 2017). The topic of trigonometry also has an important role outside the field of mathematics education, namely contributing to the development of science and technology and in everyday life such as measuring the height of buildings or buildings, flight engineering, helping to create a robot, and playing a role in the health sector (Emmanouil, Wei, & Dai, 2016;Goel, 2015;Jelatu et al, 2019;Mulyawati, Salmawati, Subianto, & Wafdan, 2017;Yang & Sianturi, 2017). In addition, the trigonometry topic has an important role because it is the topic that is tested as the final assessment in learning mathematics (Brijlall & Niranjan, 2015;Law, Shahrill, & Mundia, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Mobile learning is one of the answers to education reform [29]. Mobile learning helps students in creating social interactions.…”
Section: Android-based Mobile Learningmentioning
confidence: 99%
“…Dwi (2016), throughout her many years of research, reported that the development of cellular technology in the world of education has undergone some adaptation (i.e., changes in the learning environment that are different from the previous ones). Cooperative learning designs are even more adaptive, in which students learn more independently using smartphones and collaboration Think Pair Share (TPS) Leaning Model with Android-based m-Learning affects understanding trigonometric concepts in pre-service teachers (Jelatu, Kurniawan, Kurnila, Mandur, & Jundu (2019).…”
Section: Introductionmentioning
confidence: 99%